Unionization, industry concentration, and economic growth - Colin R. Davis; Ken'ichi Hashimoto; Ken Tabata (Osaka University, Institute of Social and Economic Research (ISER), 2021)
This paper examines how unionization affects economic growth through its impact on industry concentration in a two-country model of international trade and endogenous productivity growth. Knowledge spillovers link firm-level productivity in innovation with geographic patterns of industry ensuring a faster rate of output when industry is relatively concentrated in the country with the greater labor supply. We show that stronger bargaining power in the relatively large country increases the rate of output growth when labor unions are employment-oriented, but decreases the rate of growth when unions are wage-oriented. We then calibrate the model using labor market data for the United States and the United Kingdom and study the effects of falling union bargaining power on industry location patterns, output growth, and national welfare.
Keywords: F43; O30; O40; 330; Labor Union Bargaining Power; Industry Concentration; Knowledge Diffusion; Endogenous Productivity Growth; Endogenous Market Structure